2018
DOI: 10.1177/1120700018781759
|View full text |Cite
|
Sign up to set email alerts
|

Narcotic use and total hip arthroplasty

Abstract: Preoperative narcotic use is the most significant patient specific risk factor for prolonged postoperative narcotic use. POUs and PPUs are at a significantly higher risk of postoperative infection and revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Earlier, we found that analgesic drug consumption is reduced after hip and knee arthroplasty at the population level [36], and that obesity, a higher number of comorbidities, gender (women more than men), and preoperative use of analgesics were associated with the postoperative use of opioids, NSAIDs, or acetaminophen [38]. Previous studies have almost exclusively focused on opioid consumption, although psychiatric disorders, worse preoperative pain, and catastrophizing have also been associated with increased consumption of opioids after joint arthroplasty [4, 12, 22, 24, 25, 27, 32, 42, 43]. These factors have also been correlated with persistent pain [10, 28–30, 37, 45].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we found that analgesic drug consumption is reduced after hip and knee arthroplasty at the population level [36], and that obesity, a higher number of comorbidities, gender (women more than men), and preoperative use of analgesics were associated with the postoperative use of opioids, NSAIDs, or acetaminophen [38]. Previous studies have almost exclusively focused on opioid consumption, although psychiatric disorders, worse preoperative pain, and catastrophizing have also been associated with increased consumption of opioids after joint arthroplasty [4, 12, 22, 24, 25, 27, 32, 42, 43]. These factors have also been correlated with persistent pain [10, 28–30, 37, 45].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent pain may also lead to the increased consumption of analgesics [8]. To date, however, only a limited number of large-scale studies have been conducted on the trajectories of analgesic consumption and the risk factors associated with increased analgesic consumption after surgery [9][10][11][12][13][14][15][16][17][18][19][20][21], even though the risks for adverse events of opioids and non-steroidal anti-inflammatory drugs increase in long-term use [22][23][24], especially in elderly patients with comorbidities. Motivated by the ongoing opioid prescription crisis [25], most recent studies have focused on opioid use after joint replacement and reported higher odds for prolonged postoperative opioid use in association with psychiatric disorders, preoperative opioid use, worse preoperative pain, younger age, cardiac disease, and undergoing knee (compared to hip) surgery [9][10][11][12][13][14][15][16][17]26].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent pain may also lead to the increased consumption of analgesics (8). To date, however, only a limited number of large-scale studies have been conducted on the trajectories of analgesic consumption and the risk factors associated with increased analgesic consumption after surgery (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), even though the risks for adverse events of opioids and non-steroidal anti-inflammatory drugs increase in long-term use (22)(23)(24), especially in elderly patients with comorbidities. Motivated by the ongoing opioid prescription crisis (25), most recent studies have focused on opioid use after joint replacement and reported higher odds for prolonged postoperative opioid use in association with psychiatric disorders, preoperative opioid use, worse preoperative pain, younger age, cardiac disease, and undergoing knee (compared to hip) surgery (9,10,(14)(15)(16)(17)(18)(19)(20)26).…”
Section: Introductionmentioning
confidence: 99%